Risk factors for lung function decline in a large cohort of young cystic fibrosis patients. Issue 8 (9th June 2015) - Cogen, Jonathan; Emerson, Julia; Sanders, Don B.; Ren, Clement; Schechter, Michael S.; Gibson, Ronald L.; Morgan, Wayne; Rosenfeld, Margaret; for the EPIC Study Group
Summary Objective To identify novel risk factors and corroborate previously identified risk factors for mean annual decline in FEV1% predicted in a large, contemporary, United States cohort of young cystic fibrosis (CF) patients. Methods Retrospective observational study of participants in the EPIC Observational Study, who were Pseudomonas‐negative and ≤12 years of age at enrollment in 2004–2006. The associations between potential demographic, clinical, and environmental risk factors evaluated during the baseline year and subsequent mean annual decline in FEV1 percent predicted were evaluated using generalized estimating equations. Results The 946 participants in the current analysis were followed for a mean of 6.2 (SD 1.3) years. Mean annual decline in FEV1% predicted was 1.01% (95%CI 0.85–1.17%). Children with one or no F508del mutations had a significantly smaller annual decline in FEV1 compared to F508del homozygotes. In a multivariable model, risk factors during the baseline year associated with a larger subsequent mean annual lung function decline included female gender, frequent or productive cough, low BMI (<66th percentile, median in the cohort), ≥1 pulmonary exacerbation, high FEV1 (≥115% predicted, in the top quartile), and respiratory culture positive for methicillin‐sensitive Staphylococcus aureus, methicillin‐resistant S. aureus, or Stenotrophomonas maltophilia. Conclusions We have identified a range of risk factors for FEV1 decline in a large cohort of young, CF patients who were Pa negative at enrollment, including novel as well as previously identified characteristics. These results could inform the design of a clinical trial in which rate of FEV1 decline is the primary endpoint and identify high‐risk groups that may benefit from closer monitoring. Pediatr Pulmonol. 2015; 50:763–770. © 2015 Wiley Periodicals, Inc.